Environmental risk assessment of PPP application in European soils and potential ecosystem service losses considering impacts on non-target organisms - Urionabarrenetxea, Erik; Casás, Carmen; Garcia-Velasco, Nerea; Santos, Miguel J.G.; Tarazona, Jose V.; Soto, Manu (Ecotoxicology and environmental safety, 2023)
The use of Plant Protection Products (PPPs) is leading to high exposure scenarios with potential risk to soil organisms, including non-target species. Assessment of the effects of PPPs on non-target organisms is one of the most important components of environmental risk assessment (ERA) since they play crucial functions in ecosystems, being main driving forces in different soil processes. As part of the framework, EFSA is proposing the use of the ecosystem services approach for setting specific protection goals. In fact, the services provided by soil organisms can be impacted by the misuse of PPPs in agroecosystems. The aim of this work was to assess PPPs potential risk upon ecosystem services along European soils, considering impacts on earthworms and collembola. Four well-known (2 insecticides-esfenvalerate and cyclaniliprole- and 2 fungicides - picoxystrobin and fenamidone-) worst case application (highest recommended application) were studied; exploring approaches for linked observed effects with impacts on ecosystem services, accounting for their mode of action (MoA), predicted exposure, time-course effects in Eisenia fetida and Folsomia sp. and landscape variability. The selected fungicides exerted more effects than insecticides on E. fetida, whereas few effects were reported for both pesticides regarding Folsomia sp. The most impacted ecosystem services after PPP application to crops appeared to be habitat provision, soil formation and retention, nutrient cycling, biodiversity, erosion regulation, soil remediation/waste treatment and pest and disease regulation. The main factors to be taken into account for a correct PPP use management in crops are discussed. •Different ESs provided by soil fauna are affected after PPP application in crops.•Soil variability, PPPs properties, and spp. behaviour are key for PPP management.•More accurate toxicity tests would improve the use of ES approach in regulatory RA.